Class Management Strategies To Improve Islamic Tarikh Learning Outcomes At Mdta Al-Ikhlas - Euis Latipah; Cep Ramdan Hidayat; Elsa Safitri Zahra (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to examine classroom management strategies in improving student learning outcomes in the subject of Tarikh Islam at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Ikhlas Bojongpicung, Cianjur. The teaching of Tarikh Islam at the institution faces methodological challenges and limited facilities, resulting in low academic achievement among students. This research adopts a descriptive qualitative approach with a phenomenological method. Data collection techniques include observation, semi-structured interviews, and documentation, which were analyzed using the Miles and Huberman model. The findings reveal that classroom management strategies were implemented systematically, including seating arrangements, structured time allocation, group discussions, and the use of simple learning media. Supporting factors include student enthusiasm, teacher experience, and institutional support. The main obstacles stem from students' varied abilities, limited instructional media, and large class sizes. Nevertheless, the applied strategies effectively enhanced student engagement, evaluation scores, and learning responsibility. Periodic evaluations further strengthen the effectiveness of classroom management in achieving the learning objectives of Tarikh Islam.